EFEKTIFITAS MEDIA PEMBELAJARAN BERBASIS LOOSE PARTS PADA STEAM UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN BERPIKIR KRITIS ANAK TK AL MUBAROK BOLO TAHUN PELAJARAN 2021/2022 - Iswatini; Achmad Buchori; Aryo Andri Nugroho (STKIP Subang, 2023)
The background that drives this research is that teachers experience difficulties in stimulating problem-solving abilities in terms of symbolic thinking, including mentioning number symbols. Children experience confusion when the teacher asks the child to name the number symbols on the number cards provided by the teacher. In stimulating critical thinking skills in children, teachers experience difficulties in generating children's interest in asking questions during learning activities. Children tend to be quiet when teachers stimulate them during scientific activities and/or other activities during the teaching and learning process. The problem in this research is whether loose part learning media is effective in improving the problem solving and critical thinking abilities of Al Mubarok Kindergarten children. The aim to be achieved in this research is to determine the effectiveness of loose part learning media on children's problem solving and critical thinking abilities. This type of research is quantitative research. The population in this study were students at Al Mubarok Kindergarten. The sample from this research was group A students at Al Mubarok Kindergarten. The number of respondents consisted of 14 students from group B1 and 15 students from group B2. The data in this research was obtained through questionnaires and observations.The research results show the following correlation values: The t test for the control group's problem solving ability shows a sig. 0.06 > 0.05, meaning there is no significant difference in the average value of the control group's problem solving abilities. The t test of the experimental group's problem solving ability showed a sig value. 0.000 < 0.05, meaning there is a significant difference in the average value of the experimental group's problem solving ability. The t test of the average critical thinking ability value of the control group shows a sig value. 0.06 > 0.05, meaning there is no significant difference in the average value of the control group's problem solving abilities. The t test for the average critical thinking ability of the experimental group shows a sig value. 0.000 > 0.05, meaning there is a significant difference in the average value of the critical thinking ability of the experimental group. Thus, it can be concluded that loose part learning media is effective in improving children's problem solving and critical thinking abilities.